THE INFLUENCE OF ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER SATISFACTION THROUGH LOYALTY AS AN INTERVENING VARIABLE AMONG GENERATION Z - Hadi, Abdul; Haris, Abdul (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to examine the influence of Electronic Customer Relationship Management (E-CRM) on customer satisfaction, with customer loyalty as a mediating variable among Generation Z. The method used is Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data obtained through questionnaires. The results indicate that E-CRM does not have a direct significant effect on customer satisfaction, with a path coefficient of 0.045, t-statistic of 0.616, and p-value of 0.538. However, E-CRM significantly affects customer loyalty, with a path coefficient of 0.744, t-statistic of 10.768, and p-value of 0.000. Additionally, customer loyalty has a significant effect on customer satisfaction, with a path coefficient of 0.823, t-statistic of 12.673, and p-value of 0.000. The mediation test shows that customer loyalty mediates the effect of E-CRM on customer satisfaction, with a path coefficient of 0.612, t-statistic of 7.355, and p-value of 0.000. The model fit test resulted in an SRMR value of 0.086, NFI of 0.765, and Chi-Square of 199.075, indicating that the model has moderate fit. The managerial implication of this study is the importance for companies to enhance customer loyalty through more effective E-CRM, as loyalty is proven to be key in increasing customer satisfaction.